2019
DOI: 10.12890/2019_001044
|View full text |Cite
|
Sign up to set email alerts
|

Behçet syndrome and Crohn’s disease – what are the differences?

Abstract: Behçet syndrome (BS) is a variable vessel vasculitis that has pleiotropic manifestations. A 43-year-old male with a previous diagnosis of Crohn’s disease (CD) presented with deep venous thrombosis and bilateral superficial femoral artery aneurysms. A diagnosis of BS was made, and the patient was treated aggressively with immunosuppressive therapy and bilateral bypass surgery, attaining a favourable outcome. CD has many features that overlap with BS, and it may be challenging to distinguish between these two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Behçet's disease (BD) is a chronic multisystem variable vessel vasculitis 1 and tends to be more severe in men 2 . A high prevalence is reported in countries along the ancient silk road, stretching from Asia to the Mediterranean countries, but is not confined to these geographic locations 3 . Ocular, vascular, and central nervous system (CNS) involvements are the major causes of BD morbidity and mortality 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Behçet's disease (BD) is a chronic multisystem variable vessel vasculitis 1 and tends to be more severe in men 2 . A high prevalence is reported in countries along the ancient silk road, stretching from Asia to the Mediterranean countries, but is not confined to these geographic locations 3 . Ocular, vascular, and central nervous system (CNS) involvements are the major causes of BD morbidity and mortality 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is challenging to make a differential diagnosis between intestinal BD and CD at early presentation because these two diseases share many similarities. 1,10,19 Studies on the comparison of pathological characteristics of GI biopsy specimens between BD and CD are scarce, and intestinal biopsies have not been systematically analyzed, especially in patients with ileocecal ulcers. In a study on upper GI biopsy specimens from 50 CD patients and 34 BD patients, Akemoto et al found that in H. pylori-negative patients, focal gastric neutrophilic infiltration and wide duodenal gastric foveolar metaplasia were important in distinguishing CD from BD.…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to make a differential diagnosis between intestinal BD and CD at early presentation because these two diseases share many similarities 1,10,19 . Studies on the comparison of pathological characteristics of GI biopsy specimens between BD and CD are scarce, and intestinal biopsies have not been systematically analyzed, especially in patients with ileocecal ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…A study has reported that the thrombosis prevalence among patients with CD is 5.7% ( 20 ). In addition, BD is frequently misdiagnosed as CD in adults ( 21 ). Overall, CD has many features that overlap with BD, and as our case shows, distinguishing between these two conditions can be challenging.…”
Section: Discussionmentioning
confidence: 99%